The Background of ἐκκλησία Revisited. (December 2015) - Beale, G.K.
There has been recent debate about the background and origins for Paul's use of the word ἐκκλησία: is it to be understood primarily against an LXX or Greco-Roman background? This article is an attempt to present further evidence that there is, indeed, a clear Septuagint background for Paul's use, especially his multiple uses of 'church [assembly] of God' (ἐκκλησία τοῦ θεοῦ). Signiﬁcant parallels occur in Philo's writings, which provide a precedent for Paul's use. This does not mean that there is no Greco-Roman inﬂuence on Paul's use of the phrase, although the limits of the study allow only a relatively brief exploration of this possible background.